Afat, Mammadova - (:unkn) unknown (My University, 2026)
Afat MammadHuseyn Mammadova graduated from the Azerbaijan Civil Engineering Institute in 1984 with a degree in Industrial and Civil Engineering. From 1984 to 1986, she worked as an Engineer at the Baku Branch of the Soyuzproekt Institute. Since January 1989, she has been working at the Azerbaijan University of Architecture and Construction (AzUAC), where she has held various academic positions in the fields of occupational safety, construction economics, and economic theory and marketing. Since 2005, she has been working at the Department of Economic Theory and Marketing, where she currently holds the position of Associate Professor. From 2013 to 2016, she also served as Deputy Dean of the Faculty of Construction Economics. In 2007, she successfully defended her dissertation, Economic Aspects of the Formation and Development of the Housing Market in Azerbaijan, and in 2008 was awarded the degree of Candidate of Economic Sciences (PhD in Economics). She attained the academic title of Associate Professor in 2015. Dr. Mammadova is the author of 1 monograph, 1 textbook, 2 teaching manuals, 1 methodological manual, and more than 200 scientific and methodological publications, including articles in internationally recognized impact-factor journals. Her research interests include housing markets, construction economics, and economic development.